THE INFLUENCE OF LITERACY AND INCOME ON PEOPLE’S DECISIONS TO HAVE INSURANCE AND PENSION PROGRAMS - Anggraini, Dyah Prita; Aldila Nur Indah Berliana Ratam (Nusantara Hasana Journal, 2025)
This study aims to determine wether there is a positive and significant relationship between insurance literacy or pension programs and people’s decisions to have insurance or pension programs, wether there is a positive and significant relationship between income and people’s decisons to have insurance or pension programs, and wether there is a positive and significant relationship between insurance literacy or pension programs and income with people’s decisions to have insurance and pension programs. The subjects of this study were respondents from the webinar “Insurance Literacy in Maintaining Finansial Stability”. The method used is the Pearson Product Moment correlation tehnique to determine the relationship between each literacy variable and income to people’s decisions to have insurance or pension programs. From the test results, it was obtained that there was a positive and significant relationship between literacy and people’s decisions to have insurance or pension programs, there was a positive and significant relationship between income and people’s decisions to have insurance literacy or pension programs, income, and people’s decisions to have insurance or pension programs. Results of this study provided information for insurance industry that people will buy insurance if they have sufficient income and a good literacy about insurance and pension programs.